A BUSINESS PROCESS MODEL REDESIGN METHOD LEVERAGING DESIGN THINKING: FRAMEWORK DEVELOPMENT AND CASE STUDY APPLICATION - Suratno, Bambang; Eka Putra, Daffa Dienata Satria (Journal of Industrial Engineering Management, 2025)
The rapid evolution of information technology has significantly influenced the redesign of business processes to enhance efficiency and effectiveness. The adoption of information systems may necessitate the redesigned business process of a company. This study explores the integration of design thinking methodologies with BPI framework to design a structured design thinking method for business process redesign. The proposed method emphasizes customer-centric design principles and employs root cause analysis, value-added analysis, Business Process Modeling Notation (BPMN), and flow analysis in different phases. To validate the method, a demonstration using a case study of a redesigned recruitment business process in a talent acquisition division of a company was conducted. The results are that using the method can identify critical weaknesses in the company's existing business process (As-Is), such as inefficiencies in internal hiring, prolonged recruitment cycles, and lack of integration in approval and selection management systems. The proposed process model (To-Be) was designed by separating sourcing from hiring workflows and leveraging integrated Applicant Tracking Systems (ATS) with Human Resources Information Systems (HRIS). Evaluations of the redesigned process through flow analysis and simulation revealed significant efficiency gains: cycle time was reduced by 91.46%, cost reduced by 7.95%, and substantial improvements in average and maximum process times. These findings highlight the potential of combining design thinking with process modeling to enhance organizational workflows and meet dynamic industry demands